Family Influence and Career Adaptability: The Mediating Role of Future Time Perspective - Andini, Fellycia Ayu; Josephine, Abbigail; Riasnugrahani, Missiliana (Universitas Trunojoyo Madura, 2025)
This study investigates the correlation between family influence and career adaptability, with the future time perspective as a mediator, in final-year students residing in Bandung. We used the snowball sampling technique to collect data from 386 final-year students of D3, D4, and S1 programs. This study used the Future Time Perspective Scale, with a validity value of 0.30-0.648 and a reliability value of 0.834, the Family Influence Scale, with a validity value of 0.326-0.698 and a reliability value of 0.865, and the Career Adapt-Abilities Scale-Short Form, with a validity value of 0.561-0.759 and a reliability value of 0.896. The data analyzed using the Hayes Process Model 4 method revealed that the future time perspective partially mediates the relationship between family influence and career adaptability. The findings indicate that students who receive support from their families regarding financial, informational, and personal beliefs have a better outlook on their future. Such support enables them to identify their career goals, explore their potential and future work environment, and plan their career effectively. Students actively engaged in career preparation activities also had higher career adaptability. These students were more proactive in identifying obstacles and preparing for future career transitions after graduation.